THE USE OF FINANCIAL AND NON-FINANCIAL PERFORMANCE MEASURES IN EVALUATING STRATEGIC PERFORMANCE - Mohammed Oleiwi Al chlaihawi (Scholar Express Journals, 2022)
The research aims to determine the extent to which financial and non-financial performance measures are used in Iraqi organizations and to clarify the importance of using these measures, as well as enhancing knowledge and skills related to the latest strategic performance evaluation tools. Dimensions so that it can measure all the forces affecting the performance of the organization and its ability to achieve its strategy
Keywords: Performance Measures; Evaluating Strategic Performance